ANALISIS PELAKSANAAN REHABILITASI SOSIAL DAN KEAGAMAAN PADA MASA PANDEMI COVID-19 - Dotrimensi, Dotrimensi; Saefulloh, Ahmad; Lion, Eddy; Offeny, Offeny; Irfan Musthafa, Ahmad (Lembaga Penelitian dan Pengabdian Masyarakat Institut Agama Islam Al-Khairat Pamekasan, 2021)
The purpose of this reserach to examine and analyze the implementation of social and religious rehabilitation during the COVID-19 pandemic for Narcotics addicts at the Galilea Drug Rehabilitation Center in Palangka Raya, Central Kalimantan. In addition, what impacts arise as a result of the COVID-19 pandemic on the implementation of the existing rehabilitation program at the Rehabilitation Center. The study was conducted qualitatively through a descriptive analysis approach with purposive sampling technique through interviews with the management of the rehabilitation center, guardians of addicts, and representatives of addicts who have completed their rehabilitation period. The results showed that the social rehabilitation program in the form of a Therapeutic Community (TC) was the application of a structured environmental control method to change behavior in the context of a responsible community between fellow residents as well as helping oneself. Religious programs carried out during the COVID-19 pandemic are the development of thought and spirituality